Tren Penelitian Perilaku Bermasalah pada Anak Broken Home - Khanafiah, Melly; Putri, Mariyana Eka; Nadya, Izzati; Puriani, Risma Anita; Novirson, Rizki (Lembaga Yasin AlSys, 2025)
This study aims to analyze research trends related to problematic behavior in children from broken homes using the library research method. Problematic behaviors in children, such as aggression, juvenile delinquency, and emotional difficulties, are often associated with dysfunctional family dynamics, particularly in the context of broken homes. Through a literature review, this research identifies patterns, causative factors, and impacts of such problematic behaviors, as well as intervention approaches proposed in previous studies. The analysis reveals that factors such as lack of parental care, family conflict, and emotional instability are the primary triggers of problematic behavior in children. Additionally, this study highlights a growing academic interest in psychological and educational approaches to addressing this issue. The findings are expected to contribute to the development of further research and serve as a reference for practitioners in designing effective interventions for children from broken homes.